Relationship between first lactation milk yield and pre-partum udder measurements in crossbred heifers - CHAKI, E K; GHOSH, N; SHIT, N K; MAJUMDER, S C (The Indian Journal of Animal Sciences, 2013)
The pre-partum udder measurements of 50 crossbred heifers at different stages of pregnancy were taken to study their relations with 50 days first lactation milk yicld (FLMY) and peak yield. All the udder characters showed increasing pattern with advancement of pregnancy. However. udder length (UL). udder width (UW) and udder depth (UD) at all stages of pregnancy showed highly significant ( P < 0,01) correlations with both 50 days FLMY and peak yield. Other traits related to placement of teats also showed their significance at certain stages of pregnancy. Most ofthe udder measurements in between 61/2 and 8 months of pregnancy showed highcr association with 50 days FLMY and peak yield. It can be concluded that udder measurements iri pregnant Heifers also provide valuable basis for assessing future milk yield.